A SURVEY ON THE READING DIFFICULTIES OF K-12 LEARNERS IN SELECTED TAGALOG-SPEAKING PROVINCES: BASIS FOR INTERVENTION - DECENA, ANNALYN J. (International Journal of Arts, Sciences and Education, 2021)
Reading plays a vital role in all human activities. The development of those skills needed to produce learners who are good readers is one of the ultimate goals of every teacher especially those in the basic education. Filipino leaners take several assessment processes in school wherein reading is a key area. It was in 2018 when selected 15-year-old learners took the PISA and the country ranked the lowest in Reading. This study employed a mixed-method of research in trying to know the reading difficulties of learners from kindergarten to senior high school. An online survey questionnaire was used to gather data supported by unstructured interview with teachers. With ninety-two (92) teachers participating in this research (with the majority teaching in elementary level), it was found out that the reading difficulties of learners when it comes to oral reading are the following presented from the most to the least observed: poor pronunciation, slow rate in reading, word-by-word reading, repetition, omission, insertion, reversal, and substitution. When it comes to comprehension, almost hundred percent of the participants agreed that inadequate understanding is a problem along with inadequate vocabulary knowledge. The teachers contend that if the reading material has a lot of unfamiliar words or vocabulary, the students lost their interest and understanding of the text. With all these findings, it was concluded that comprehension is really a problem for learners. The researcher humbly recommends that teachers provide a lot of exercises suited to the capacity of the learners which could help them overcome these difficulties in reading especially their problem with comprehension.